Automatic top loader washing machine related injury. a report of four cases with serious injury - Kwan, M.K.; Saw, A.; Ahmad, T.S. (2005)
We are reporting four cases of serious washing machine related injury that presented within a period of 5 months. All patients were young children with the mean age of 9 year-old and three had their dominant hand injured. The washing machines involved were the automatic top loader type and all injuries occurred during the spinning phase. Serious automatic washing machine injury is not uncommon in Malaysia. We feel that there is a need to improve the safety features especially during the spinning phase. The operating instructions and safety precautions on the washing machine should be displayed in different languages that can be understood well. Parents should also aware of the potential risks of this seemingly benign household appliance.